2019
DOI: 10.1101/gad.324905.119
|View full text |Cite
|
Sign up to set email alerts
|

Clustered telomeres in phase-separated nuclear condensates engage mitotic DNA synthesis through BLM and RAD52

Abstract: Alternative lengthening of telomeres (ALT) is a telomerase-independent telomere maintenance mechanism that occurs in a subset of cancers. One of the hallmarks of ALT cancer is the excessively clustered telomeres in promyelocytic leukemia (PML) bodies, represented as large bright telomere foci. Here, we present a model system that generates telomere clustering in nuclear polySUMO (small ubiquitin-like modification)/polySIM (SUMO-interacting motif) condensates, analogous to PML bodies, and thus artificially engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
139
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 86 publications
(105 reference statements)
7
139
0
Order By: Relevance
“…APBs have been proposed to play a critical role in ALT by clustering telomeres and DNA repair factors together, thus concentrating substrates and enzymes required for recombination-based telomere elongation (Henson et al 2002;Cesare and Reddel 2010;Chung et al 2011;Chung et al 2012;Min et al 2019;Verma et al 2019). In agreement with this hypothesis, it has recently been shown that telomeres can be elongated during mitosis in APB-like foci in a process termed mitotic DNA synthesis MiDAS (Ozer et al 2018;Min et al 2019). Moreover, depletion of PML by siRNA has been shown to reduce telomere elongation (Osterwald et al 2015).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…APBs have been proposed to play a critical role in ALT by clustering telomeres and DNA repair factors together, thus concentrating substrates and enzymes required for recombination-based telomere elongation (Henson et al 2002;Cesare and Reddel 2010;Chung et al 2011;Chung et al 2012;Min et al 2019;Verma et al 2019). In agreement with this hypothesis, it has recently been shown that telomeres can be elongated during mitosis in APB-like foci in a process termed mitotic DNA synthesis MiDAS (Ozer et al 2018;Min et al 2019). Moreover, depletion of PML by siRNA has been shown to reduce telomere elongation (Osterwald et al 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Recent work in mammalian cells has paralleled the work done in yeast, revealing that ALT-positive cancer cells display a type I-like ALT mechanism that is RAD51-dependent and characterized by telomere clustering and recombination-mediated telomere synthesis (Cho et al 2014;Ramamoorthy and Smith 2015). In addition, ALT-positive mammalian cells also display RAD51-independent type II-like mechanisms of telomere elongation characterized by telomere synthesis in the G2/M phase of the cell cycle Min et al 2017;.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations